Tobacco smoking and multiple sclerosis: effects on occurrence, progression and mortality - Manouchehrinia, Ali (2014)
Multiple Sclerosis is an immune mediated disease of the central nervous system associated with a wide range of mainly irreversible psychological and physical disabilities in young adults. Despite the invaluable knowledge gained from the research into the disease, its aetiology and mechanism of progression are poorly understood. The natural history of multiple sclerosis is complex and there are still many unanswered questions in respect to the risk factors associated with its development and the way that the disease evolves with age. Over the years numerous theories about the disease aetiology have been postulated, but the one that best describe the disease, on the basis of our current understanding, both in terms of susceptibility and progression is the gene-environment hypothesis. According to this hypothesis, multiple sclerosis occurs as the result of an exposure(s) to some unknown environmental factor(s) in genetically susceptible individuals. In multiple sclerosis, it has been hypothesised that tobacco smoking is associated with an increased risk of the disease occurrence and adverse effects on the progression of disabilities. Despite the relatively large amount of data on the adverse effect of smoking on multiple sclerosis risk and clinical course, data from a large population based cohort was lacking. The aim of the current work was to investigate the influence of tobacco smoking on the natural history of the disease from the risk of occurrence to mortality.